Treatment strategies in patients with gynecological sarcoma: Results of the prospective intergroup real-world registry for gynecological sarcoma in Germany (REGSA-NOGGO RU1). Issue 2 (11th January 2023) - Roser, Eva; Harter, Philipp; Zocholl, Dario; Denschlag, Dominik; Chekerov, Radoslav; Wimberger, Pauline; Kurzeder, Christian; Hasenburg, Annette; Muallem, Mustafa-Zelal; Mustea, Alexander; Emons, Guenter; Zeimet, A G; et al.
Abstract : Objective: Gynecological sarcomas account for 3% of all gynecological malignancies and are associated with a poor prognosis. Due to the rarity and heterogeneity of gynecological sarcomas there is still no consensus on optimal therapeutic strategies. This study's objective was to describe the treatment strategies used in patients with gynecological sarcomas in the primary course of disease. Methods: The German prospective registry for gynecological sarcoma (REGSA) is the largest registry for gynecological sarcomas in Germany, Austria and Switzerland. Primary inclusion criteria for REGSA are histological diagnosis of sarcoma of the female genital tract, sarcoma of the breast or uterine smooth muscle tumors of uncertain malignant potential (STUMP). We evaluated data of the REGSA registry on therapeutic strategies used for primary treatment from August 2015 to February 2021. Results: A total of 723 patients from 120 centers were included. Data on therapeutic strategies for primary treatment were available in 605 cases. Overall, 580 (95.9%) patients underwent primary surgery, 472 (81.4%) of whom underwent only hysterectomy. Morcellation was reported in 11.4% (n=54) of all hysterectomies. A total of 42.8% (n=202) had no further surgical interventions, whereas an additional salpingo-ophorectomy was performed in 54% (n=255) of patients. An additional lymphadenectomy was performed in 12.7% (n=60), an omentectomy in 9.5% (n=45) and intestinal resection in 6.1% (n=29) of all patients. Among 448 patients with available information, 21.4% (n=96) received chemo- or targeted therapies, more commonly as single-agent treatment than as drug combinations. Information about anti-hormonal treatment was available for 423 patients, among which 42 (9.9%) received anti-hormonal treatment, 23 (54.8%) of whom with low-grade endometrial stroma sarcomas. For radiotherapy, data of 437 patients were available, among which 29 (6.6%) patients underwent radiotherapy. Conclusion: Our study showed that treatment of patients with gynecologic sarcomas is heterogeneous. Further trials are needed along with more information on treatment modalities, therapy response and patient-reported outcomes to implement new treatment strategies.